2017
DOI: 10.1097/md.0000000000007273
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis mimicking metastatic progression of pancreatic neuroendocrine tumor

Abstract: Rationale:Pancreatic neuroendocrine tumors (PNETs) account for less than 5% of all pancreatic tumors. PNETs develop from pancreatic endocrine islet cells and have a variable range of malignant potential. These neoplasms tend to have a slower growth rate than exocrine tumors and may remain undetectable for years. Achieving a correct diagnosis and staging is of key importance for the optimal management of the disease and requires experience with the disease, an accurate clinical status evaluation and a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The authors suggested that the increased risk of cancer following sarcoidosis may be due to the fact that sarcoidosis causes chronic inflammation, which eventually gives rise to malignancy [ 7 ]. Moreover, similar (but not identical) combinations of tumors identified in this case, have been previously reported, such as pancreatic neuroendocrine tumors with extra-pancreatic sarcoid [ 8 , 9 ]. However, a definite link between sarcoidosis and malignancy is yet to be confirmed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The authors suggested that the increased risk of cancer following sarcoidosis may be due to the fact that sarcoidosis causes chronic inflammation, which eventually gives rise to malignancy [ 7 ]. Moreover, similar (but not identical) combinations of tumors identified in this case, have been previously reported, such as pancreatic neuroendocrine tumors with extra-pancreatic sarcoid [ 8 , 9 ]. However, a definite link between sarcoidosis and malignancy is yet to be confirmed.…”
Section: Discussionsupporting
confidence: 81%
“…More ominous diagnoses such as adenocarcinoma must be ruled out since symptoms may be nonspecific and mimic cancer, and pancreatic sarcoidosis can present concomitantly with pancreatic cancer [ 10 ]. Furthermore, sarcoidosis that does not involve the pancreas can co-present with primary tumors of the pancreas, including neuroendocrine tumors [ 8 ] and pseudopapillary tumors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between sarcoidosis and different types of malignancies has been previously described [2–10]. Carcinoid or neuroendocrine tumours (NETs) are rare tumours and association with sarcoidosis has been reported in the literature [11–25]. NETs can arise from any organ but most commonly from lung and small intestine [26].…”
Section: Introductionmentioning
confidence: 99%